A comparative study of different anatomical position, clinical presentation and USG findings with operative findings in patients of appendicitis - Patel, K. G.; Thekdi, Pukur I.; Nathwani, Parth; Patel, Nita K. (International Journal of Research in Medical Sciences, 2017)
Background: The objective was to find out and compare accuracy of USG findings with that of per-operative findings of location & status of appendix, to compare , evaluate & study the signs and symptoms in different varieties of appendicitis, to compare & study pre, per & post op follow up of patients with such different location of appendix undergoing appendicectomy and to study the type of appendicitis responsible for inflammation/infection by histopathological examination of different locations of appendix. Methods: The present study was prospective, observational and longitudinal. Protocol of the procedure was formed along with Performa, Patient Information Sheet and Informed Consent Form. The present study was carried out in surgery department of C.U. Shah medical college, Surendranagar; Gujarat state. The study was carried out from 1st October 2010 till 31st September 2012. A total of 100 cases were subjected to clinical assessment using signs, symptoms and laboratory criteria, histopathology and also the position of the appendix, which were recorded in the proforma. All patients were subjected to ultrasound examination by a qualified radiologist to exclude any other associated pathology and also to confirm the diagnosis. At surgery the Position of the appendix was first identified before disturbing the structures and the position of the appendix. After completion of the appendectomy the specimen was subjected to histopathological examination by the qualified pathologist only those cases, which were proved as, appendicitis by the histopathology were included in the study. Results: Out of 100 cases, a total of 62 cases presented with clinical features suggestive of retrocaecal appendicitis, out of which 51 had typical presentation & 11 had atypical presentation with overall sensitivity of 72.9%, followed by pelvic position which had a sensitivity of 15.29% in which 8 patients had typical presentation & 5 had atypical presentation. All modalities (clinical presentation + lab investigations + USG + intra operative + histopathology) patients were 47; with clinical presentation + lab investigations + USG + intra operative patients were 51; with clinical presentation + lab investigations + USG patients were 57; with clinical presentation + lab investigations patients were 69 and with only clinical presentation patients were 85. Conclusions: A total of five modalities that were used for the diagnosis of position of appendix & appendicitis, i.e. clinical features, lab Ix, ultrasound, intraoperative findings & histopathology, only 47% of cases all the modalities were positive. So the diagnosis of position of appendix & appendicitis is a combination of all the modalities and not just dependent on one basis.